Composition, concentration and distribution of linear alkylbenzenes in surface sediments from selected locations in Malaysia - Alkhadher, Sadeq Abdullah Abdo (2017)
Linear alkylbenzenes (LABs) are a group of organic chemical markers that primarily constitute raw materials of linear alkylbenzene sulfonates (LAS) type detergents. LABs are ubiquitous compounds and of high concern due to their intensive usage in detergents around the world. The objective of this study is to investigate the composition, concentration and distribution of LABs in surface sediment samples from selected locations in Malaysia and to identify possible sources and biodegradation of LABs in the sediment samples of the studied areas using the ratio of internal (I) and external (E) isomers of LABs (I/E ratios). The correlation between LABs concentration and total organic carbon (TOC) is also investigated. Thirty two surface sediments were collected from developed and less developed areas around Peninsular Malaysia, that is at Port Dickson, Muar River, Pulau Merambong, the Johor Bahru coast, the Kim Kim River as well as Brunei Bay in Sabah and Brunei waters. The sediment samples were analyzed using gas chromatography-mass spectrometry (GC-MS). The compositional profiles of LABs showed that the long chain alkylbenzenes (C13+C14) were higher than short chain alkylbenzenes (C11+C10). The C13 homolog was the most abundant type of LAB found in sediments of the studied areas.The concentrations of LABs found ranged from 7.1 to 255.8 (ng.g-1 dw), representing low to moderate levels. The results showed higher levels of LABs in the Muar River and Kim Kim estuary than those investigated in 2004 at the same areas. LABs found in this study are lower than those detected in other places of Southeast Asia such as at Kolkata, India and Jakarta, Indonesia, whereas they are consistent with the levels found in other parts of the world such as Humber, UK, and Santos Bay, Brazil. The results also showed that LABs were strongly correlated with TOC in Port Dickson, Muar River, Merambong and Brunei Bay in Sabah and Brunei waters and weakly correlated in Johor Bahru coast and the Kim Kim River. The I/E ratio of LABs was used as an indicator of LABs biodegradation in the aquatic environment. The results from I/E ratios were from 0.6 to 4.1 and indicate that the LABs come from a range of raw, primary to secondary treated effluents. Based on the results from the LABs concentrations, it is recommended that different sites of Malaysia should be monitored and managed to reduce the levels of LABs entering the marine environment.